SHAYKH MUHAMMAD ARSYAD AL-BANJARI’S THOUGHT ON EDUCATION (JOURNAL OF INDONESIAN ISLAM, 2011)
Shaykh Muhammad Arsyad Al-Banjari is a religious central figure who has key roles in introducing new religious ideas in South Kalimantan. In this context, his thoughts are not only in the area of religion but also in education. There are at least four significant points of Al-Banjari’s thought on education. First, the educational paradigm was under the umbrella of neo-Sufism which emphasized on bayani, ‘irfani and burhani. Second, the institutional education introduced is a semi-formal education in which the study was concentrated in one place. Third, the teaching methods used are macro and micro. Macro method includes contextualization, centralization and integralization. Micro method covers uswah hasanah, halaqah, lecturing, and question and answer. Above all, the material for religius study in Al-Banjari’s period was deeper and wider compared to the era before Shakh  his arrival. The use of various books for studying was so illustrative